How to Deal with the Fabricated Hadith: Some Notes for Hadith Dispersion in Social Media - Abur Hamdi Usman; Rosni Wazir; Mohd Norzi Nasir (Insaniyat : Journal of Islam and Humanities, 2022)
In Islam, the fabricated hadith is the least acknowledged hadith. The scholars unanimously reject this hadith and forbid its recitation without identifying its status. Fabricated hadith’s core perversion is its justification for the Prophet Muhammad’s assassination (PBUH). Falsification of hadith has harmed numerous facets of life, including faith, religious legislation, and acts of devotion. Additionally, the number of false hadiths is growing daily. This chilling reality has become a concern due to the widespread dissemination of such hadiths through modern technology. The dissemination of falsified hadiths via social media has emerged as a new issue that new-generation Muslims must take seriously, particularly individual awareness, knowledge, ethics, and morals.This paper will emphasize the hadith’s history and falsification aspects, assess its dispersion tendencies using more advanced media, and recommend many tips for preventing further dissemination. Using a qualitative method, this study found several guidelines to ensure the dispersion of fabricated hadith is handled properly, such as not believing in anything quickly, ensuring authenticity before sharing, and providing advice to admit mistakes in spreading the fabricated hadith. In this regard, we encourage academic scholars to conduct research on fabricated hadiths in order to preserve the purity and authority of the Prophet’s hadiths as the second Islamic source for Muslims.